Immunohistochemical staining of plastic embedded bone marrow trephine biopsy specimens after microwave heating. Issue 9 (September 1995) - McCluggage, W G; Roddy, S; Whiteside, C; Burton, J; McBride, H; Maxwell, P; Bharucha, H
Abstract : AIMS--To investigate (1) whether adequate immunohistochemical staining can be achieved on sections cut from plastic embedded bone marrow trephine biopsy specimens after microwave heating in citrate buffer; and (2) whether this immunohistochemical staining is comparable with that achieved on routine sections cut from paraffin wax embedded trephine biopsy specimens after decalcification procedures. METHODS--Sixty five consecutive bone marrow trephine biopsy specimens of more than 1 cm in length were divided transversely into two equal parts. One part was processed in paraffin wax followed by decalcification. The other part was embedded in the epoxyresin Polarbed 812 followed by the cutting of 1 micron sections. Both parts underwent immunohistochemical staining by an identical panel of antibodies. With Polarbed 812 plastic embedded sections, microwave heating in citrate buffer was undertaken before the application of antisera. RESULTS--On sections cut from plastic embedded material, immunohistochemical staining was generally satisfactory, easy to interpret and comparable with that achieved with paraffin wax embedded material. Exceptions were antibodies to neutrophil elastase and CD61 where immunostaining was consistently negative on plastic embedded sections. Immunohistochemical staining for CD20 was consistently more reliable on plastic embedded sections. CONCLUSIONS--The results provide evidence that, with few exceptions, satisfactory immunohistochemical staining is possible on plastic embedded bone marrow trephine biopsy specimens after microwave heating in citrate buffer. This, combined with the advantage of superior cellular morphology with semi-thin (1 micron) sections of plastic embedded material, make such embedding procedures the preferred method for the processing of bone marrow trephine biopsy specimens.